(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2001)
Maximum positive ellipticity parameter’s values were received for rat liver chromatin preparations in control and under in vivo and in vitro actions of steroid hormone hydrocortisone and peptide hormone insulin. It was shown, that in vivo action of both hormones lead to significant increase of this parameter’s value. In vitro action of hormones doesn’t changee the value of the mentioned parameter of hormones doesn’t reveal additivity. Specific antagonism of hydrocortisone and insulin action at chromatin is observed. It is noteworthy that a change of the parameter’s value of the maximum positive ellipticity is observed in total chromatin preparations as well as in its active fraction.